Local knowledge on landscape sustainable-hydrological management reduces soil CO2 emission, fire risk and biomass loss in West Kalimantan Peatland, Indonesia - DWI ASTIANI; MOHAMMAD J TAHERZADEH; EVI GUSMAYANTI; TRI WIDIASTUTI; BURHANUDDIN BURHANUDDIN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Astiani D, Taherzadeh MJ, Gusmayanti E, Widiastuti T, Burhanuddin. 2019. Local knowledge on landscape sustainable-hydrological management reduces soil CO2 emission, fire risk and biomass loss in West Kalimantan Peatland, Indonesia. Biodiversitas 20: 725-731.  Local knowledge in managing peatlands, especially in the area of peat hydrology, has been practiced through generations to manage peatlands for agriculture and small scale gardens. Farmers in West Kalimantan have developed the way to conserve water by making simple dams using soil or woody plants to hold water from the peat upstream areas on small channels or rivers. To reduce puddles during rain or tides, people make small trenches, so-called parit cacing in the middle of the larger channel. The trench cross-section size is ~30-40 cm2. This channel can maintain the peat water level to the extent of the depth of the channel. These channels, at the same time, are useful, for a clear, easy land ownership border for one farmer family land. The results of CO2 emissions assessment at various water levels on the peatland landscape demonstrate that the landscape which surrounded by the parit cacing trenches can maintain lower CO2 emissions compared to the one that has deeper water levels. The knowledge to develop this channel has also reduced the risk of peatland fire hazard and the amount of peat biomass loss on a fire event. An assessment on the effect of water level on the loss of peat biomass when burned, reduce 30-78% loss risks if compared to water table depth of 60-80cm, which is assumed as general practices on peatland recently. The practices of the knowledge on peatlands hydrology management can reduce the risk of peatland soil CO2 emission as well as loss of peat mass through decomposition and during peat fires.